Congenital perineal defect with rectal duplication and extreme hypospadias-a rare association - Mrinal Arora; Noor Ullah Zargar; Anurag Krishna (SpringerOpen, 2022)
Abstract Background Congenital perineal hernia is an extremely rare entity with only 10 cases having been reported in literature. We report a newborn with exposed bowel loops coming out through a defect in the perineum to the right of the median raphe and propose the term perineoschisis for this abnormality. The exposed bowel loops were a sequestered segment of colon. The baby also had extreme perineal hypospadias and left undescended testis. Case presentation A term neonate, born of caesarean section, was noted at birth to have exposed bowel loops visible in the perineum. The bowel loops were not covered by any membrane. To avoid injury to the exposed bowel loops and setting in of infection, the baby was taken up for emergency surgery. At laparotomy, the bowel loops were traced from duodeno-jejunal junction to ileocecal junction and sigmoid colon and rectum. No loops were seen herniating outside from the abdomen through the perineum opening. The extruded bowel loops were sequestered and ending blindly close to the rectum. The sequestered bowel loops were excised completely and perineum reconstruction was done. Conclusion The extruded bowel loops would appear to be a form of colonic duplication with the duplicated colonic loops herniating outside through an opening in the perineum. Since the bowel loops were lying to the right of median raphe and were not covered by hernia sac or any other membrane we propose the term perineoschisis for this abnormality. The baby also had extreme hypospadias with a perineal meatus, bifid scrotum and penoscrotal transposition. This association of herniated duplicated colon with extreme hypospadias is hitherto unreported to the best of our knowledge.